The Expression of Solute carrier family members Genes in Mouse Ovarian Developments - O, Lee-Gyun; Park, Chang-Eun (Korean journal of clinical laboratory science, 2017)
Granulosa cells, which surround the oocyte within the ovarian follicle, play an essential role in creating conditions required for the development of oocytes and follicles. The solute carrier family (SLC) is comprised of influx transporters of steroidal hormones, various drugs, and several other substrates. The differential expression of selected DEGs was confirmed using in situ hybridization analysis. SLC23A3 and SLC39A10 were highly expressed in the ovary. The SLC39A10 gene was expressed in the primordial follicle stage, but SLC23A3 was expressed in the growing follicle stage. Contrastingly, the expression of SLC23A3 was increased in granulosa cells at the growing follicle stage. The differential expressions of SLC23A3 and SLC39A10 between the primordial and primary follicles were additionally confirmed by using follicle isolations. The gene expression profile from the present study may provide insight for future studies on the mechanism(s) involved in primordial-primary follicular transition and suggestions to promote follicular development in ovarian dysfunction. KCI Citation Count: 0